Chronic Respiratory Symptoms and Lung Abnormalities Among People With a History of Tuberculosis in Uganda: A National Survey. (18th September 2018) - van Kampen, Sanne Christine; Jones, Rupert; Kisembo, Harriet; Houben, Rein M G J; Wei, Yinghui; Mugabe, Frank R; Rutebemberwa, Elizeus; Kirenga, Bruce
Abstract: Background: People with pulmonary tuberculosis are at risk of developing chronic respiratory disorders due to residual lung damage. To date, the scope of the problem in high-burden tuberculosis countries is relatively unknown. Methods: Chronic respiratory symptoms (cough and phlegm lasting >2 weeks) and radiological lung abnormalities were compared between adults with and without a history of tuberculosis among the general population of Uganda. Multivariable regression models were used to estimate odds ratios (ORs) with adjustment for age, gender, smoking, education, setting, and region. Random effects models accounted for village clustering effect. Results: Of 45293 invited people from 70 villages, 41154 (90.9%) participated in the survey. A total of 798 had a history of tuberculosis and, among them, 16% had respiratory symptoms and 41% X-ray abnormalities. Adjusted ORs showed strong evidence for individuals with a history of tuberculosis having increased risk of respiratory symptoms (OR, 4.02; 95% confidence interval [CI], 3.25–4.96) and X-ray abnormalities (OR, 17.52; 95% CI, 14.76–20.79), attributing 6% and 24% of the respective population risks. Conclusions: In Uganda, a history of tuberculosis was a strong predictor of respiratory symptoms and lung abnormalities, before older age and smoking. Eliminating tuberculosis disease could reduce the prevalence of chronic respiratory symptoms as much as eliminating smoking. Abstract : Among the general population of Uganda, ex-tuberculosis patients are at high risk of chronic cough, phlegm, chest pain, hemoptysis, and chest X-ray abnormalities. A history of tuberculosis was a greater predictor of chronic respiratory problems than old age or smoking.